2006
DOI: 10.1207/s15327914nc5401_4
|View full text |Cite
|
Sign up to set email alerts
|

Berry Phenolics: Antimicrobial Properties and Mechanisms of Action Against Severe Human Pathogens

Abstract: Antimicrobial activity and mechanisms of phenolic extracts of 12 Nordic berries were studied against selected human pathogenic microbes. The most sensitive bacteria on berry phenolics were Helicobacter pylori and Bacillus cereus. Campylobacter jejuni and Candida albicans were inhibited only with phenolic extracts of cloudberry, raspberry, and strawberry, which all were rich in ellagitannins. Cloudberry extract gave strong microbicidic effects on the basis of plate count with all studied strains. However, fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
325
0
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 454 publications
(342 citation statements)
references
References 61 publications
6
325
0
11
Order By: Relevance
“…Plenty of studies have shown that plant origin foods are important sources of bioactive compounds, also known as phytochemicals (Dembitsky et al, 2011a, b;Gayosso-García Sancho et al, 2011;Hossain & Rahman, 2011;Nohynek et al, 2006). Among the most common bioactive compounds occurring in plant origin foods are phenolic compounds (PCs), carotenoids, xanthophylls, and chlorophylls, among others (Hossain & Rahman, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plenty of studies have shown that plant origin foods are important sources of bioactive compounds, also known as phytochemicals (Dembitsky et al, 2011a, b;Gayosso-García Sancho et al, 2011;Hossain & Rahman, 2011;Nohynek et al, 2006). Among the most common bioactive compounds occurring in plant origin foods are phenolic compounds (PCs), carotenoids, xanthophylls, and chlorophylls, among others (Hossain & Rahman, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there has been a classification of PCs according their ease of extraction: extractable (EPC) and non extractable (NEPC) (Bravo, 1998). Tropical fruits are plenty and diverse, and recent research suggests that an appropriate consumption of them may confer different health benefits (Das et al, 2012;Leifert & Abeywardena, 2008;Nohynek et al, 2006). These compounds can also have antioxidant capacity (ADXC) and protect against oxidative stress in different body tissues, if they are adequately released from the food matrix and absorbed in the small intestine (Palafox-Carlos et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemicals present in black raspberries reduce vascular endothelial growth factor (VEGF) expression, which contributes to metastasis inhibition [23,24]. Many raspberry and blackberry phenolics exhibit antimicrobial [25,26] and antiviral [27] activities. Due to a high content and large diversity of health-beneficial phenolic compounds, raspberry and blackberry fruits can be regarded as natural functional food.…”
Section: Introductionmentioning
confidence: 99%
“…Strawberry extract inhibited the growth of gram-negativebacteria, especially Escherichia coli, and Salmonella enterica ser. Typhimurium, Campylobacter jejuni, and Candida albicans (Nohynek et al, 2006;Puupponen-Pimiä et al, 2001. In addition, the antimicrobial effect on 1D TLC bioassay plates for ethanol extract of unripe fruit was greater than that of the extract of ripe fruit (Terry et al, 2004).…”
Section: Introductionmentioning
confidence: 93%